TANGGAP DIRI MASYARAKAT PESISIR DALAM MENGHADAPI BENCANA EROSI PANTAI (Studi Kasus Masyarakat Desa Bedono Kabupaten Demak) - Sanjoto, Tjaturahono Budi; Sunarko, Sunarko; Parman, Satyanta (Jurnal Geografi, 2016)
Coastal erosion is a natural process that occurs in the Village District Bedono Sayung Demak regency. Thispaper aims to examine the efforts of local communities toward coastal erosion. The method used field surveyinstruments to guide in-depth-interviewing, direct observation, and documentation. Sources of informationderived from community residents, community leaders, and government officials. Based on the researchresults known that communities efforts toward abrasion in the area were done by planting mangroves,elevating the house floor, making the stage home, while government support in the form of mangroveseedlings, repairing trails, making the walls of surge protectors, as well as providing new land for relocationof the residents.